The mesozooplankton of the Patos Lagoon Estuary, Brazil: trends in community structure and secondary production. Issue 1 (2nd January 2017) - Teixeira-Amaral, Priscila; Amaral, Waldemar José Appolinário; de Ortiz, Danielle Ortiz; Agostini, Vanessa Ochi; Muxagata, Erik
ABSTRACT: The zooplankton abundance and composition of the Patos Lagoon Estuary (PLE) reflects the local hydrological regime with alternating periods of flood, freshwater run-off and mixing of water. However, little is known about the interannual zooplankton variations and secondary productivity of this community. We sampled zooplankton monthly at two stations within the estuary from April 2009 to March 2013. The brackish/marine calanoid copepod Acartia tonsa was found to play an important role in the PLE, with secondary production values of 1.17 mg C m −3 day −1 being comparable with the high values achieved in other estuaries worldwide. During the study period, the greatest change in the community structure was observed in the spring-summer under El Niño influence when the prolonged terrestrial run-off combined with higher temperatures allowed the establishment of a freshwater community that was largely composed of the calanoid copepod Notodiaptomus incompositus, cyclopoids and cladocerans. The freshwater copepod N. incompositus, which replaced A. tonsa, was second in importance with regard to production (mean 0.13 C m −3 day −1 ). Our work emphasizes the ecological importance of long-term zooplankton monitoring studies and provides the first assessment of N. incompositus production.